PDGF-C and PDGF-D in ocular diseases. (August 2018) - Kumar, Anil; Li, Xuri
Abstract: PDGFs and their receptors are critical regulators of numerous tissues and organs, including the eye. Extensive studies have shown that PDGFs and their receptors play critical roles in many ocular neovascular diseases, such as neovascular age-related macular degeneration, retinopathy of prematurity, and proliferative vitreoretinopathy. In addition, PDGFs and PDGFRs are also important players in ocular diseases involving the degeneration of retinal neuronal and vascular cells, such as glaucoma and retinitis pigmentosa. Due to their critical roles in the pathogenesis of many blinding ocular diseases, the PDGFs and PDGFRs have been considered as important target molecules for the treatment of eye diseases. PDGF-C and PDGF-D are relatively new members of the PDGF family and are potent angiogenic and survival factors. Recent studies have demonstrated their important roles in different types of eye diseases. Thus, modulating PDGF-C and PDGF-D activities may have therapeutic values for the treatment of ocular neovascular and degenerative diseases. This review mainly summarizes the recent advances on PDGF-C and PDGF-D biology in relationship to some major ocular diseases.